Kemampuan Menulis Naskah Drama dengan Menggunakan Teknik Pemodelan (Modeling) Siswa Kelas VIII.1 SMPN 4 Lengayang Kabupaten Pesisir Selatan - Aprilisma, Silvia; Nursaid, Nursaid; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2013)
The research was motivated by five bases. First, students are not able to develop an ideas or looking for new ideas at writing plays. Second, in the writing, students could not use Bahasa Indonesia properly and correctly. Third, students also did not have good understanding of playwriting materials as they played in the class. Fourth, lecturing students to write a play make most students got saturated. Fifth, evaluation results show that only half of the students able to write a play. This study aimed to determine the ability of the students at writing plays using modeling techniques (modeling). The students are of the class VIII.1 of SMPN 4 Lengayang, South Coast District of West Sumatera.            The type of this research is quantitative. The technigue used this study are pre with the research design of pre-test and post-test. The population is 27 students of the class VIII.1 of SMPN 4 Lengayang using a random technique class or purposive sampling. Data collected through performance tests. Data were analyzed with particular steps. First, read and check out the plays written by the students. Second, scoring. Third, convert the scores to values.  Fourth, group the values in scale of 10. Fifth, group the values into a frequency distribution table. Sixth, determine the arithmetic mean of the students  skill at writing plays.Results of data analysis showed that the ability to write a play before using the modeling technique is average (C) 58.52 and the ability to write a play after using modeling techniques are classified as good (B) 72.7 so there are clear difference between before and after this research . Based on the t test known that t value is 4.52 while the t table is 1.71, proved that t > t table. The t-test research show that the ability to write a play with modeling techniques of the students of the class VIII.1 SMPN 4 Lengayang is better than the ability to write a play without using modeling techniques.